Design of backhaul routes in VRRP networks of MPLS VPN - Haolun WANG (Dianxin kexue)
In the process of flattening metropolitan area network,in order to improve the reliability of MPLS L3VPN services,OLT devices can be planned as VRRP branch nodes.This design could probably induce traps of backhaul routes.Two separate methods of switching backhaul routes were proposed.One is a strict method based on checking the reachability of OLT devices,the other is a simplified method based on the priority of routes.The experimental results show that,handover latency is between 2~ 8 s.These proposed methods of switching backhaul routes,can effectively prevent traps of backhaul routes,and improve the reliability of services.